Genotypic difference in secondary metabolism‐related enzyme activities and their relative gene expression patterns, osmolyte and plant hormones in wheat. Issue 4 (3rd December 2019) - Dugasa, Mengesha T.; Chala, Idesa G.; Wu, Feibo
Abstract : Salinity and drought are the two most important and frequently co‐occurring abiotic factors. A greenhouse pot experiment was carried out on two contrasting wheat genotypes (Jimai22, salt tolerant; Yangmai20, salt sensitive) to analyze the effect of drought (4% soil moisture content, D) and salinity (100 mM NaCl, S) either individually or combined on secondary metabolism‐related enzyme activities and osmolytes. Results showed that drought, salinity and their combination (D + S) caused increases in phenylalanine ammonialyase (PAL, EC 4.3.1.24) activities compared with controls with a greater enhancement in Jimai22 than Yangmai20. Polyphenol peroxidase (PPO, EC 1.14.18.1) and shikimate dehydrogenase (SKDH, EC 1.1.1.25) activities increased more in Jimai22 both under salinity alone and D + S stresses. The D + S combination increased cinnamyl alcohol dehydrogenase (CAD, EC 1.1.1.195) activity and glycine betaine (GB) under both 10 and 4% soil moisture contents (SMC), and elevated abscisic acid (ABA), indole‐3‐acetic acid (IAA) and flavonoid contents at 4% SMC in Jimai22, contents of the compounds remained unchanged in Yangmai20. The treatment with salinity alone at both SMCs significantly increased callose and flavonoid contents in Jimai22 more than in Yangmai20, as compared to controls. In addition, the total phenol content at 4% SMC increased in the salt‐tolerant genotype more. Moreover, total tocopherol under salinity alone and D + S at 4% SMC and chitinase activity under salinity at both SMC remarkably increased in Jimai22 while non‐significant change observed in Yangmai20. Also, the expression of genes related to secondary metabolism ( PAL, PPO, CAD, SKDH, and GB ) was more induced in Jimai22 than Yangmai20 under D + S, and lower accumulation of H2 O2 and O2 − also occurred. Our findings suggest that high tolerance to D + S stress in Jimai22 was closely related to enhanced secondary metabolism‐related enzyme activities and osmolytes such as PAL, CAD, PPO, SKDH, GB, total tocopherol, callose, plant hormones and their transcript level, which may beneficial to lower the reactive oxygen species (ROS) accumulation.